Meteorite search by JARE-39 in 1998-99 season - Kojima, Hideyasu; Kaiden, Hiroshi; Yada, Toru (National Institute of Polar Research, 2000)
P(論文) A meteorite search party composed of eight men of the 39th Japanese Antarctic Research Expedition (JARE) collected 4136 meteorites on bare ice areas around the Yamato Mountains and the Belgica Mountains in 1998-99 field season. Approximately 4100 meteorites have been collected around the Yamato Mountains. They include many kinds of rare meteorites. By classification in the field, 2 lunar meteorites, 3 irons, 4 stony irons, 15 ureilites, 37 diogenites, 63 eucrites, 29 unclassified achondrites and 160 carbonaceous chondrites are distinguished. The number of irons is very small for such a great number of the meteorites. We also searched for meteorites around the Belgica Mountains. Twenty-one meteorites have been collected. All of them are ordinary chondrites. departmental bulletin paper